Assessment of U.S. Domestic Airline Fuel Efficiency since 2010. Issue 1 (January 2015) - Kwan, Irene; Rutherford, Daniel
Aircraft are responsible for about 2.5% of anthropogenic carbon dioxide (CO2 ) emissions globally. Total aircraft CO2 emissions are expected to triple by 2050 if present trends continue. Surprisingly little public information is available about the fuel efficiency, and therefore carbon intensity, of U.S. airlines. This research seeks to address this gap by assessing the fuel efficiency of major airlines serving the U.S. domestic market from 2010 to 2012 by using airline-reported fuel and operations data. A frontier model was used to develop an efficiency metric that accounts for the fuel that airlines burn to provide both mobility (passenger miles traveled) and access (frequency of service and number of airports served). Recognizing that many main-line carriers receive service from their regional partners, the fuel efficiency assessment incorporates the fuel and operations of regional carriers into the fuel and operations of their respective main-line carriers. Airlines that operate circuitous routes are also distinguished. Alaska, Spirit, and Southwest were among the most fuel-efficient airlines, in contrast to less-efficient carriers such as Allegiant and American, which consumed an estimated 26% more fuel than Alaska on equivalent operations in 2012. Airlines that were the most efficient overall did not necessarily transport a given passenger more efficiently between each city–city pair, because of differences in technology utilization and operations. From 2010 to 2012, the average rate of improvement was estimated to be 1.1% per year, short of existing climate protection goals, highlighting the importance of continued efforts in both technology and policy to reduce emissions from aviation.